Are Informal Self-Employment and Informal Employment as Employee Behaviorally Distinct Labor Force States? - Luca Flabbi; Mauricio Tejada (Institute of Labor Economics (IZA), 2023)
The paper performs both a parametric and non-parametric analysis to address a fundamental question in the growing literature using search models to study labor market informality: should informal self-employment and informal employment as employee be considered two different labor market states? Both the non-parametric and the parametric tests strongly reject equality between the two states, cautioning against aggregating them in a common "informality state." The parametric model indicates the source of the difference in the high dispersion of informal self-employment income and in the low duration of informal employee jobs.
Keywords: J46; J64; O17; 330; labor market frictions; search and matching; informality; self-employment